2004
DOI: 10.1037/0021-9010.89.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Counterproductive Behavior at Work: A General Perspective.

Abstract: Counterproductive work behaviors have predominantly been investigated at relatively narrow levels, with the focus limited to subsets of the behavioral domain as well as to specific explanatory approaches. This study took a broader perspective with respect to both dependent and independent variables. A sample of German employees from 2 organizations reported on their levels of general counterproductive behavior (GCB). In predicting GCB, M. R. Gottfredson and T. Hirschi's (1990) theory of self-control as a gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
370
0
24

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(411 citation statements)
references
References 56 publications
17
370
0
24
Order By: Relevance
“…Indeed, research has shown a clear link between work stressors such as interpersonal conflict, workload, role conflict, and role ambiguity, on the one hand, and CWB on the other (for a review, see . Personal factors such as self-control (Marcus & Schuler, 2004) and negative affectivity (Douglas & Martinko, 2001) may also be important factors in this process. A limitation of the available research in this area is that a comprehensive model which tries to explain the process leading to CWB has not yet been attempted.…”
mentioning
confidence: 99%
“…Indeed, research has shown a clear link between work stressors such as interpersonal conflict, workload, role conflict, and role ambiguity, on the one hand, and CWB on the other (for a review, see . Personal factors such as self-control (Marcus & Schuler, 2004) and negative affectivity (Douglas & Martinko, 2001) may also be important factors in this process. A limitation of the available research in this area is that a comprehensive model which tries to explain the process leading to CWB has not yet been attempted.…”
mentioning
confidence: 99%
“…That is, when employees encounter what they perceive to be injustice (e.g., unfair compensation, lack of respect), they may take actions to help to restore justice by acting in ways that intentionally hurt an organization (Fox, Spector, and Miles, 2001;Cohen-Charash and Spector, 2001;Marcus and Schuler, 2004). Perceptions of justice are divided into three distinct types: distributive justice (fairness of distributions of rewards or resources); procedural justice (fairness of the way outcomes are determined and whether one has a voice in the process); and interactional justice, which is divided further into interpersonal justice (treating people with dignity and respect) and informational justice (receiving clear explanations about the procedures used to determine an outcome) (Greenberg, 1993;Colquitt, 2001;Fox, Spector, and Miles, 2001;and Morrison and Robinson, 1997).…”
Section: Attitudes and Perceptionsmentioning
confidence: 99%
“…Opportunity is a necessary precondition for deviant behav ior to occur (e.g., Gottfredson & Hirschi, I 990;Marcus & Schuler, 2004). Because, personal control entails extensive discretion at work, it therefore affords individuals greater opportunity to engage in unsafe behavior and take shortcuts without interference from others.…”
Section: Personal Controlmentioning
confidence: 99%
“…With less oversight and supervision, individuals are more likely to develop bad habits and can more easily bypass or ignore regulations as they have both less fear of reprisal and greater occasion to develop alternative, and possibly unsafe, methods of perfom1ance. Conversely, low levels of personal control wi ll curtail chances to perfom1 deviant behavior (Marcus & Schuler, 2004), as employee behaviors w ill be monitored and high ly regulated. There fore, similar to findings that job autonomy strengthens the relationship between job stressors and deviant behavior (Fox et al, 2001 ), we suggest that personal control provides emotionally exhausted workers the means necessa1y to alleviate strain by developing and enacting unsafe shortcuts and workarounds.…”
Section: Personal Controlmentioning
confidence: 99%